Pengembangan Keterampilan Desain dalam Menumbuhkan Wirausahawan Anyaman Bambu Halus di Parakanhonje, Tasikmalaya - Santi Susanti; Iwan Koswara; Rachmaniar Rachmaniar (Jurnal Pengabdian Pada Masyarakat, 2022)
DESIGN SKILLS DEVELOPMENT IN CULTIVATING FINE WOVEN BAMBOO ENTREPRENEURS IN PARAKANHONJE, TASIKMALAYA. The target of this PPM is fine bamboo artisans in Parakanhonje Village, Sukamaju Kaler, Indihiang District, Tasikmalaya City, West Java. Fine bamboo crafts are a long-standing characteristic of bamboo crafts in Parakanhonje. We relate our PPM to education and the economy. Related to education, this PPM provides training on the craft and design of fine bamboo in Parakanhonje as part of an effort to regenerate artisans so the fine bamboo woven remains sustainable. In terms of economy, the improvement of design skills is expected to increase the economic empowerment of the artisans in Parakanhonje. This PPM activity presented speakers and PPM Fikom Unpad Team and conducted online on Zoom application, which was attended by bamboo artisans in Tasikmalaya and its surroundings. The results of this PPM show that the craftsmen gain knowledge of design development through information literacy skills conveyed by the speaker. This PPM motivates bamboo artisans to maintain the fine-woven bamboo craft in Parakanhonje.